Native aortic valve derived extracellular matrix hydrogel for three dimensional culture analyses with improved biomimetic properties. (5th April 2019) - Nehrenheim, Laura; Raschke, Silja; Stefanski, Anja; Barth, Mareike; Selig, Jessica Isabel; Barbian, Andreas; Fernández-Colino, Alicia; Stühler, Kai; Mela, Petra; Albert, Alexander; Lichtenberg, Artur; Akhyari, Payam
Abstract: Introduction : Calcific aortic valve disease (CAVD) is the most common acquired heart valve disease with complex underlying pathomechanisms that are yet not fully understood. Three-dimensional (3D) cell culture models as opposed to conventional two-dimensional (2D) techniques may reveal new aspects of CAVD and serve as a transitional platform between conventional 2D cell culture and in vivo experiments. Methods : Here we report on fabrication and characterization of a novel 3D hydrogel derived from cell-free native aortic valves. A detailed analysis containing protein composition, rheological behavior, cytotoxic and proliferative effects as well as results of 3D cell culture experiments are presented. Moreover, this aortic valve derived hydrogel (AVdH) is compared to commercially available biological extracellular matrix (ECM) components to evaluate and classify AVdH with respect to other currently used ECM solutions, i.e. Collagen type I and Matrigel ® . Results : On the biochemical level, a complex composition of native proteins was detected. Using different techniques, including mass spectrometry with Gene Ontology network and enrichment analysis, different fundamental biological functions of AVdH were identified, including peptidase-, peptidase inhibitor-, growth- and binding activity. No cytotoxic effects were detected and AVdH showed positive effects on cell growth and proliferation in vitro when compared to Collagen type I and Matrigel ® . Conclusion : These results suggest AVdH as an organotypic ECM supporting sophisticated 3D cell culture model studies, while mimicking the native environment of the aortic valve to a greater level for enhanced in vitro analyses.